Truth or Consequences of the Justice System Reform Council: An English Language Bibliography from Japan’s Millennial Legal Reforms - Levin, Mark A.; Mackie, Adam (Zeitschrift für Japanisches Recht, 2013)
INTRODUCTION This bibliography is drawn from a project originated by Professor Setsuo Miyazawa of Aoyama Gakuin Law School in conjunction with a symposium titled Successes, Failures, and Remaining Issues of the Justice System Reform in Japan organized by Hastings College of the Law and the Hastings International and Comparative Law Review. We began with a short list from Professor Miyazawa and then crowd-sourced our data gathering by broadcasting a request to the East Asian Law Collaborative Research Network of the Law and Society Association. We also carried out independent research drawing upon a variety of online resources. We consider it remarkable that there have been nearly 150 separate scholarly publications that have looked into these important events. Our preliminary criteria for listings were: 1) English-language publications, 2) mainly published in 2001 or later, 3) dealing with the issues addressed by Japan’s Justice System Reform Council, and 4) published in an academic journal or in a book as a chapter rather than mass media sources. We then cut with a sharper knife to eliminate constitutional law issues not directly related to justice system reform; publications published in 2001 or later, but drawing solely upon circumstances prior to the Justice System Reform Council report; matters dealing with Japanese financial deregulation; corporate governance reform; and the revision of the Code Of Civil Procedure, all of which took place roughly contemporaneously with the Justice System Reform Council events but were essentially unrelated to them. As co-compilers of this bibliography, we would like to extend our thanks to Professor Miyazawa as the originating force behind this project, Professors Daniel Foote, Luke Nottage, and Harold Baum for sharing their extensive data sets with us, and the many scholars who have carried out their investigation into these important issues to produce the vast body of work that the bibliography presents. We hope this compilation will serve as a useful tool for researchers and others as Japan moves into its second decade under its distinctively reformed justice system.